Cleaning and infection control of airway clearance devices used by CF patients. (November 2017) - Manor, Eynav; Gur, Michal; Geffen, Yuval; Bentur, Lea
Respiratory treatment for cystic fibrosis (CF) patients includes use of respiratory devices. Contamination of airway clearance devices has not been adequately explored. We aimed to determine whether airway clearance devices are contaminated after use and whether cleaning guidelines for nebulizers are as effective for airway clearance devices. Patients brought their airway clearance devices to the clinic. Swabs from the devices were taken before and after cleaning and were cultured for bacterial counts. Total colony-forming units (CFU) was determined, and predominant colonies were identified using Matrix-Assisted Laser Desorption Ionization Time-of-Flight Mass Spectrometry technology. Thirty devices were collected from 23 patients. Most of the devices (28/30) were contaminated when brought to the clinic. Complete bacterial eradication was achieved in 15 (50%) samples and partial eradication in 9 (30%). The cleaning was totally ineffective in four samples. Median CFU decreased significantly from 1250 (IQR 25–75% 175–10.000) to 0 (IQR 25–75% 0–700) before and after cleaning ( p < 0.0001). The predominant organisms were identified in five samples only, and there was no concordance with sputum culture results. Airway clearance devices are contaminated after use, and appropriate cleaning can reduce contamination. The effect on disease progression in CF patients is unclear. There is a need for infection prevention and control guidelines for the growing number of respiratory devices.